Legal Policy and Suporting Factors of Criminal Law Enforcement Crime Prevention - Broto Laksito, FX. Hastowo; Bawono, Aji (Journal Evidence Of Law, 2024)
Law enforcement is a necessity carried out by the state in protecting its society as members, because law enforcement has the essence of upholding the values of truth and justice. Crime prevention efforts through criminal law are essentially part of criminal law enforcement efforts. Criminal law enforcement is realised through legal policy as part of national legal politics. This matter relates to various factors ranging from the formation of regulations, law enforcement officials, and the behaviour of the community itself. The focus of this article review is to explain how the criminal law enforcement policy towards crime prevention, as well as the extent to which it can support the implementation of criminal law enforcement policy. This paper review consists of several main points, namely law enforcement policy, aspects of legislation, aspects of law enforcement, and aspects of community legal culture. This study concludes that criminal law enforcement policy can be initiated by making legal products that are suitable with the social conditions of society.